MENGEVALUASI PERDA WAJIB BELAJAR DUA BELAS TAHUN DI KABUPATEN KUDUS DAN PELAKSANAANNYA PADA WARGA SAMIN - Moh Rosyid (Universitas Tanjungpura, 2022)
Human rights is the right of every one is right education. This paper observes the right of children of Samin community in Kudus especially in the field of education. Samin community is chosen for its uniqueness in maintaining their anchestor’s teaching not to go to formal school, as a way of resistance against the Dutch colonial government, despite the fact that today some of Samin community go to school and obey government regulation. The main focus of this research is the realization Government Regulation Kudus (Perda) to the required learning 12 years. Method of collecting data conducted through literature, interview, and direct observation in the field. The analysis data used is qualitative descriptive. the results of the research are (1) the required learning 12 years for community Samin did not happen, (2) Persuasive approach is important to encourage Samin community to send their children to formal education as stated by Government Regulation (PP) No 48 Year 2008 Article 15 (1), (2), and (3) Government Regulation Kudus (Perda) to the required learning 12 years must be evaluated by Ombudsman Commision.